Effect of clay turbidity on the growth and survival of kerai lampam Hypsibarbus wetmorei x Barbonymus gonionotus - Lokman, Adiba Akmal (2013)
Effect of clay turbidity on the growth performance and survival of kerai lampam was investigated during a 5-week experimental period. The experiment was conducted at the Aquaculture Research Centre, Puchong, Universiti Putra Malaysia. There were four turbidity treatments, each with four replicates: 0ppm (treatment 1), 50ppm (treatment 2), 150ppm (treatment 3), and 300ppm (treatment 4). Each aquarium was stocked with 20 individuals of kerai lampam (2-3 inches size) and filled with 60 L of water. Fish were fed by artificial pellets at 5% of body weight twice a day. The data was analysed by using SPSS, Duncan’s multiple range test, and one-way ANOVA (P=0.05). During the experiment, water quality was measured. Dissolved Oxygen (DO) was maintained above 4mg/L, whereas pH range was from 6.78 until 8.57 and temperature range was from 24.78°C until 27.40°C. Ammonia-Nitrogen was maintained below 2.00 mg/L. Different levels of clay turbidity did not affect the growth and survival of kerai lampam, but influenced size variation. Treatment with 150ppm of clay turbidity tended to have bigger size fish (>2g) compared to the other treatments.